2019
DOI: 10.18004/rspp.2019.diciembre.41-45
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pathogens causing acute diarrheal disease in the Asunción and Central Metropolitan area

Abstract: Prevalencia de patógenos causantes de enfermedad diarreica aguda en el área Metropolitana de Asunción y Central RESUMEN Introducción: Las enfermedades diarreicas agudas (EDA) constituyen un problema de salud pública y son una de las causas más importantes de mortalidad y morbilidad en niños a nivel mundial. O b j e t i v o : D e t e r m i n a r l a p r e v a l e n c i a d e enteropatógenos causantes de EDA en el área metropolitana de Asunción y Central. Materiales y métodos: Se realizó un estudio observacional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
1
1
0
1
Order By: Relevance
“…Our results confirm the possibility that mixed infections by two pathotypes of DEC can be detected in a sample, as mentioned in other studies (Huber et al, 2019;Odetoyin et al, 2016 ). This PCR was highly specific with the primers chosen for the detection of six categories of DEC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results confirm the possibility that mixed infections by two pathotypes of DEC can be detected in a sample, as mentioned in other studies (Huber et al, 2019;Odetoyin et al, 2016 ). This PCR was highly specific with the primers chosen for the detection of six categories of DEC.…”
Section: Discussionsupporting
confidence: 90%
“…Our study differ from other reports by Verma et al (2019), Thakur et al (2018) in India which suggested low prevalence of ETEC 6%, 5.7%. While in Huber et al (2019), ETEC was recognized ETEC as major pathotype among children less than 5 years, and in the study by Hasan et al (2020) in Dohuk /Iraq, the isolation rate of ETEC was the highest. Low-grade hygienic state of family and artificial feeding may account for this high rate of ETEC.…”
Section: Discussionmentioning
confidence: 87%
“…In Asunción and the metropolitan area, diarrheagenic Escherichia coli, Rotavirus, Campylobacter spp., Shigella spp., and Salmonella spp. have been described as the most prevalent etiological agents in children under 5 years of age (31).…”
mentioning
confidence: 99%
“…Sur para el 2015 es de 23,6 kg/persona/año, demostrando un incremento progresivo del 66% con relación a años anteriores, siendo Brasil el país con mayor consumo per ISSN: 2600-5859 Otro de los agentes patológicos predominantes en el estudio es la bacteria E. coli causante de enfermedades como: síndrome diarreico, colitis hemorrágica, síndrome urémico hemolítico y púrpura trombocitopénica trombótica, infecciones del tracto urinario y otros padecimientos infecciosos, por consumo de productos lácteos, vegetales, frutas, productos cárnicos y alimentos preparados en restaurantes y los síntomas y signos son diarrea con o sin sangre, fiebre, vómito, dolor y calambres abdominales. Este dato coincide con lo reportado porHuber et al (2019), quienes manifiestan que el síndrome diarreico es una de las enfermedades más prevalentes que origina la E. coli. De igual manera,Alarcon et al (2019) revelan que esta bacteria puede generar infecciones urinarias.…”
unclassified